2017
DOI: 10.12991/mpj.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Development of in situ poloxamer-chitosan hydrogels for vaginal drug delivery of benzydamine hydrochloride: Textural, mucoadhesive and in vitro release properties

Abstract: The use of in situ hydrogel systems for vaginal drug delivery is an important strategy in the treatment of vaginitis. The aim of this study was to develop in situ vaginal hyrogels for benzydamine hydrochloride (BNZ) which were composed of poloxamer and chitosan. The reason for development of these hydrogels was to obtain a vaginal delivery system with improved mechanical and mucoadhesive properties that could provide prolonged retention time for the treatment of vaginits. The hydrogels were also designed for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…High adhesiveness, cohesiveness and elasticity are the ideal features of a vaginal gel as these permit the localisation of an antimi-crobial agent at the targeted region and increase the performance of the formulation by allowing full structural recovery following administration. Appropriate compressibility and hardness are also crucial for vaginal application [112,114]. Similarly, Tuğcu-Demiröz developed a thermo-responsive hydrogel for the treatment of vaginitis.…”
Section: Thermo-responsive Systemsmentioning
confidence: 99%
“…High adhesiveness, cohesiveness and elasticity are the ideal features of a vaginal gel as these permit the localisation of an antimi-crobial agent at the targeted region and increase the performance of the formulation by allowing full structural recovery following administration. Appropriate compressibility and hardness are also crucial for vaginal application [112,114]. Similarly, Tuğcu-Demiröz developed a thermo-responsive hydrogel for the treatment of vaginitis.…”
Section: Thermo-responsive Systemsmentioning
confidence: 99%
“…For chitosan, this unexpected result could be due to the low molecular weight of the polysaccharide, that we used. Indeed, after comparing different types of chitosans, some authors previously showed that the increase in the chitosan molecular weight and viscosity could expand the adhesiveness of gels [69].…”
Section: Mucoadhesion Propertiesmentioning
confidence: 99%
“…under the name Pluronics ® . The most commonly used are Poloxamer 407 and Poloxamer 188 [66]. These are block copolymers made up of polyoxyethylene units and polyoxypropylene units that undergo a sol-gel transition when temperature rises.…”
Section: Strategies To Increase Residence Time On the Ocular Surfacementioning
confidence: 99%